Race profiles of rowers during the 2014 Youth Olympic Games - Cerasola, D.; Cataldo, A.; Bellafiore, M.; Traina, M.; Palma, A.; Bianco, A.; Capranica, L. (The Journal of Strength and Conditioning Research, 2018)
Among the different factors affecting the outcome of elite rowing competitions, pacing strategy plays a relevant role. The purpose of this study was to analyze the race profiles of youth athletes competing at the 2014 Youth Olympic Games over a distance of 1,000 m. According to the competition outcome of sculling and sweep events, 96 youth (17-18 years) rowers (48 male and 48 female) were divided into winner (W), not winner (NW), qualified (Q), and not-qualified (NQ) athletes. The time during the 1,000-m race distance was considered at 0-500 m (T1) and 500-1000 m (T2). The average speed of T1 and T2 were normalized in relation to the average speed of the whole race. In both sexes, W rowers showed higher (p > 0.05) T2 values (100.8 ± 0.9%) with respect to T1 (99.2 ± 0.9%) ones. Female athletes showed a higher (p = 0.05) T1 with respect to T2 in NW, Q, and NQ, whereas male athletes exhibited a higher T1 (p = 0.05) than T2 speed only in NQ. While to be admitted to the final phase of the competition, the rowers tended to favor a positive race strategy (88%); during the final phase, a difference (p = 0.43) emerged for outcome, with the majority of medalists (67%) adopting a negative race strategy. These results suggest that winners have applied a different race strategy compared with the other groups in consequence to a higher efficiency of anaerobic metabolism.